Perceptions of education for sustainable development in Egypt: Prospective changes in teaching practices - Abozaied, Hanan Salah Yusuf (AUC Knowledge Fountain, 2018)
This study explores the perceptions of university faculty members about the concept of Sustainable Development (SD) and Education for Sustainable Development (ESD). It focuses on how their different perceptions influenced their teaching practices while addressing sustainability issues with students. The participants are 18 academics in the English department under the faculty of Arts and Humanities in a private university in Egypt. They teach two academic language courses in the advanced level for undergraduates in different disciplines. The study adopts a sociocultural theoretical framework. It uses a qualitative research design. A preliminary survey was conducted at the beginning of the semester to explore faculty members perceptions, then, based on information collected from the survey, a workshop was delivered to expand discussion about SD and ESD concepts. Finally, a follow-up interview was conducted with participants who attended the workshop to explore whether or not their acquired knowledge about SD and ESD influenced their teaching methods. Results indicate that the workshop helped participants to have a clearer understanding of the concepts of SD and ESD. However, their teaching practices were not affected.